The Long and Narrow Road: An Inuit Student’s Journey Through Post-Secondary Music - Jacque, Kendra; Waterman, Ellen (Intersections, 2019)
Eurocentrism is deeply embedded in the structures governing post-secondary music, from admissions to curricula. In this article, an Inuit student from northeastern Labrador recounts her journey to and through music school, including the challenges of accessing music instruction and navigating the audition, the considerable supports she received from mentors and organizations, and the culture shock, isolation, and racial micro-aggressions she experienced in university. Several recent qualitative studies of Indigenous students’ university experiences provide context for and support our conclusion that decolonization of post-secondary music must include deep structural change to provide broader and more flexible pathways for students and curricula that respond to the needs of a pluralistic society.